1978
DOI: 10.1364/ao.17.002270
|View full text |Cite
|
Sign up to set email alerts
|

Generation of coherent cw radiation tunable from 211 nm to 216 nm

Abstract: Many spectroscopic studies require a source of coherent cw radiation tunable in the uv. Continuous wave radiation in the 257-360-nm range has been generated by sum frequency mixing, in potassium dihydrogen phosphate (KDP) and its isomorphs, selected output lines from an argon or krypton ion laser with the output of a cw dye laser. 1 Recent studies of mixing in potassium pentaborate (KB5) using pulsed laser systems 2 however suggested that cw radiation at wavelengths considerably shorter than 257 nm could be ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The shortest-wavelength cw radiation that was previously produced by SFM in a crystal is approximately 211 nm. 4 The only other technique that has been demonstrated for generation of coherent cw radiation below 200 nm is four-wave mixing in strontium vapor, at approximately 170 nm, by Freeman et al 5 A schematic of the experimental setup is shown as Fig. 1.…”
Section: Mwmentioning
confidence: 99%
“…The shortest-wavelength cw radiation that was previously produced by SFM in a crystal is approximately 211 nm. 4 The only other technique that has been demonstrated for generation of coherent cw radiation below 200 nm is four-wave mixing in strontium vapor, at approximately 170 nm, by Freeman et al 5 A schematic of the experimental setup is shown as Fig. 1.…”
Section: Mwmentioning
confidence: 99%